Physiological and Molecular Study for Some Cases of Coronary Artery Disease - Zahraa Abdali Mohammad; Ali MHussein; Hassan R Mobarek (Indian Journal of Forensic Medicine & Toxicology, 2021)
Coronary artery diseases (CAD) known as the disorders of the heart and the blood vessels, which claimed 17.1 million lives a year worldwide. to identify the correlation between the coronary artery disease and some physiological and molecular parameters in men. one hundred blood samples (5 ml) collected from coronary artery diseases patients, the Complete blood count parameters (CBC), Serum concentrations of Creatinine, Glucose, Cholesterol, Triglycerides, HDLLDL, T3 , T4 and TSH were measured in current study. Multiplex polymerase chain reaction used to determine the presence or absence of GSTM1 and GSTT1 genes in the genomic DNA and CYP1A1 as an internal control. The results of current study showed significant increase in the total WBC, Neutrophil, Lymphocyte, MCH, MCHC,PLT, MPV, PCT, creatinine, glucose, cholesterol, Triglyceride, LDL andTSH in patients group when compared with control.The percentage of coronary artery diseases were increase 47% when the GSTM1 gene absence in patients group compared with control,while no significant differences were recorded when GSTT1 gene absence and the two genes absence in patient group compared with control.The study concluded that physiological indicators may increase in patients with Coronary artery diseases .